1996
DOI: 10.1007/bf02769543
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of spin-dependent total cross-section differenceΔσ T in neutron-proton scattering at 16 MeV

Abstract: A new measurement of ∆σ T for polarized neutrons transmitted through a polarized proton target at 16.2 MeV has been made. A polarized neutron beam was obtained from the 3 H(d, n) 4 He reaction; proton polarization over 90% was achieved in a frozen spin target of 20 cm 3 volume. The measurement yielded the value ∆σ T = (−126 ± 21 ± 14) mb. The result of a simple phase shift analysis for the 3 S 1 − 3 D 1 mixing parameter ǫ 1 is presented and compared with the theoretical potential model predictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The experimental setup was similar to the one used for the ∆σ T measurement described in [6], so only brief description with more stress to the modifications will be presented here.…”
Section: Pacsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental setup was similar to the one used for the ∆σ T measurement described in [6], so only brief description with more stress to the modifications will be presented here.…”
Section: Pacsmentioning
confidence: 99%
“…The A 00nn (ϑ) measurement at 90 deg c.m. is presented by Schöberl [3,4]), while ∆σ T was measured in TUNL in the 3.65-11.60 MeV energy range (1993 [5]) and at 16.2 MeV in our laboratory (1993 [6]). Furthermore, ∆σ L has been measured at 66 MeV incident neutron energy at Villigen (1992 [7]).…”
mentioning
confidence: 99%
“…In the previous experiments on np-scattering (Prague, Charles University) [4,5], transversely polarized neutrons were produced as a secondary beam in the T(d, n) 4 He reaction with deuterons with energies up to 2.5 MeV [6]. The neutron beam with an energy E n = 16.2 MeV was emitted at an angle θ lab = 62.0 • .…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary experiments showed that the polarization and intensity of the neutron beam and also the deuteron polarization of the target are insufficient for achieving the necessary accuracy of the measurement of the cross-section difference [7]. To improve the parameters of the neutron beam, it is proposed to use the reaction T(d, n) 4 He with polarized deuterons with an energy of 100-150 keV. Also, we plan to replace the current target material (propanediol) with a novel material chemically doped with the trityl family radicals, which showed the deuteron polarization as high as P d = 0.80 [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation